THE EFFECTIVENESS OF "FLASH CARD" IN IMPROVING MOTHERS’ KNOWLEDGE ON PREGNANCY - Tatarini Ika Pipitcahyani; Citra Adityarini Safitri (Proceedings of the International Conference on Applied Science and Health, 2017)
Aims: To know the effectiveness of using flash cards as a method to educate the expecting mothers during pregnancy counselling class. Methods: The study used pre-experimental pre-test and post-test control group designed with the intervention using flash card. This study was conducted from January to September 2016 with a population of 40 pregnant women and sampling by means of accidental sampling with 10 respondent. The research was designed by using Quasi-Experiment Wilcoxon statistical techniques. Results: From Wilcoxon test, the results demonstrate a level of knowledge in the control group with a score of 0.59 sig (p>0.05). In the treatment group sig 0.05 (p>0.005) indicates a significant difference between the group using flip charts and the flash card group. From the Mann-Whitney test, the results yield sig 0.002 (p>0.005) which shows that flash card proved to increase the level of knowledge of pregnancy. Conclusion: Counselling using a flash card is an effective method to educate the expecting mothers to better understand the knowledge of pregnancy health.